Rappresentazioni sociali e costruzione di identità profes- sionali "riflessive" nei contesti psichiatrici: considerazioni formative - Valerio Ferro Allodola (Firenze University Press, 2013)
Social Representations (SR) powerfully involved in the construction of health care professionals, particularly in psychiatric contexts, encouraging - if made out by means of reflective practice - a greater understanding of our socio-cognitive reference systems of reality. Through the latter, in fact, we build our own ideas about health and disease / patient who translate later into behaviors and actions in daily practice. Analyzing the Theory of Social Representations of Moscovici, the author intends to study the process of 'translation' of the SR in behavior that characterizes the practices of professionals in mental health.